International Trade and the Tokyo Round Negotiation - GILBERT R. WINHAM (Princeton University Press, 2014)
International negotiation has become the primary mechanism by which industrial nations make trade policy. The trend in this direction started with the U.S. Reciprocal Trade Agreements Act of 1934. It was reaffirmed by the establishment of GATT in 1947, and it has continued through a succession of negotiations both under and outside GATT auspices. The Tokyo Round negotiation of 1973-79 was the seventh and largest of a postwar series of GATT multilateral negotiations. This book is a political history of that negotiation. In writing a history about a discrete event, I felt obliged to report by what process that event had come about and to analyze the substantive impact it might have had on the environment in which it occurred. This book tackles both these tasks: readers can judge for themselves to what extent it has succeeded. But in carrying out these tasks, I could not help but wonder whether what from hindsight seems so clearly to be a trend toward international negotiation would indeed continue to be a trend into the future. The past half-century has seen a growth of collective decisionmaking in international trade, and the Tokyo Round was part of that development; it will be fascinating to find out if the Tokyo Round continued that trend or if it was a turning point toward a more individualistic and nationalistic style of trade policymaking. Questions such as these were clearly beyond this book, but at least they did motivate the effort to understand contemporary trade negotiation and its meaning for the international economic system. For the ultimate answers, one must wait—impatiently—for the future to unfold. The data gathered for this book consisted mainly of personal interviews, government documents, and secondary sources. Numerous confidential interviews were conducted with government officials and international civil servants who participated in the Tokyo Round. These sources cannot be identified, although in many cases the richness of the ideas discussed in interviews surely warranted attribution. I am delighted to take this opportunity to thank my interviewees for the generous and unreciprocated concession of their time. I hope they will feel compensated with the knowledge that this book will be a lasting record of their accomplishments.